Perancangaan Rute Pengiriman Optimal dengan Vehicle Routing Problem (VRP) untuk Efisiensi Distribusi di Jaya Abadi Fruits - Ramdan, Deni Muhamad; R, Annisa Nurhikmah; Arifahyani, Elviana; Fauzi, Muchammad (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
This study focuses on optimizing the distribution routes at Jaya Abadi Fruits using the Vehicle Routing Problem (VRP) method with a Saving Matrix approach. The primary issue is the manual route management that relies solely on the drivers' memory, leading to frequent wastage of travel distance, time, and operational costs. Moreover, the stochastic nature of customer demand complicates daily supply planning and results in suboptimal fulfillment of customer needs. This research utilizes primary data collected through direct observation and interviews to gain an accurate understanding of the distribution process. The Saving Matrix analysis is applied to identify optimal routes, reducing the travel distance from 109.4 km to 61.8 km (a savings of 43.51%), cutting travel time from 4.46 hours to 2.20 hours (a savings of 50.67%), and lowering distribution costs from IDR 279,400 to IDR 231,800 (a savings of 17.04%). Keywords: Distribution, Efficiency, Saving Matrix, Vehicle Routing Problem